11-Year Study of Fentanyl in Driving Under the Influence of Drugs Casework. Issue 3 (18th May 2021) - Chan-Hosokawa, Ayako; Bierly, Jolene J
Abstract: Prior to 2017, heroin and other prescription opioids were the most prevalent opioids implicated in driving under the influence of drugs (DUID) investigation cases, and fentanyl was rarely included in the scope of toxicological analysis. Fentanyl has become the most frequently identified opioid in DUID cases, with many suspected heroin cases turning out to be only fentanyl. A review of fentanyl-positive DUID cases at NMS Labs was performed to provide prevalence information, change in concentration, patterns of combined drug use, indicators of impairment and driving behavior in order to assist with the toxicological interpretation of DUID scenarios involving fentanyl. Fentanyl-positive DUID cases received between January 2010 and December 2020 were examined. Blood results were confirmed and quantitated for fentanyl, norfentanyl and acetylfentanyl using a liquid chromatography–tandem mass spectrometry analysis with a limit of quantitation of 0.10, 0.20 and 0.10 ng/mL, respectively. Of 153, 234 blood cases examined for DUID over 11 years, fentanyl was confirmed positive in 6, 779 (4.4%) cases. However, there were significant changes in positivity over time. Fentanyl percentage positivity increased from 0.60% in 2010 to 12% in 2020. Of 5, 976 confirmed fentanyl-positive cases in 2018–2020, blood concentrations >4.0 ng/mL were observed in 44% (2018), 55% (2019) and 59% (2020) of cases. Polypharmacy was common with 87% of blood samples confirmed positive for fentanyl and at least one other compound. Stimulant was the most commonly identified drug class in cases where at least one additional drug class was present. This study illustrates the importance of including fentanyl in a routine blood DUID panel.